Education Law, Strategic Policy and Sustainable Development in Africa Agenda 2063 (Springer International Publishing, 2018)
This book outlines the findings and suggestions of the Law and Society Association's International Research Collaborations, which focused on the African Union's Agenda 2063. This outlined the ideal Africa aspired to by the year 2063: 'the Africa we want'. The authors examine socio-economic rights issues and their impact on developing a strong educational agenda that can drive Africa to realize Agenda 2063. As Africa's development has remained slow in the face of many challenges, the need to embrace good governance, rule of law and human rights obligations are major tools to realize the continent's potential. The project focuses in particular on the central place of education law and policy in achieving the goals of Agenda 2063.